Zobozdravstveno varstvo – sestavina združenega dela - Komadina, Dominik (Obzornik zdravstvene nege, 1977)
Associated labour is a broader conception of labour associated in the economic activities. In encompasses the work performed within all social activities including stomatological services. They represent an activity of special social interest and impose on the performers to get organized in conformity with the principles of the socialist self management. They are to make away with the lingering remnants of obsolete social relationship and proceed to the execution of the Law of Associated Labour.